PENGAMBILAN KEPUTUSAN PENGHINDARAN PAJAK PADA PERUSAHAAN MULTINASIONAL BERDASARKAN MULTINASIONALISM, PEMANFAATAN TAX HAVEN DAN THIN CAPITALIZATION - Ayuningtyas, Fitria; Pratiwi, Adhitya Putri (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
This study aims to analyze tax avoidance decision making in multinational companies based on multinationalism, the use of Tax Havens and Thin Capitalization. This study uses quantitative methods and uses secondary data from multinational companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. The sample used in this study used purposive sampling technique and obtained a sample of 32 companies. The data analysis method in this study uses multiple linear regression analysis with the statistical program Eviews 10. The results of this study prove that: Multinationality has a significant effect on tax avoidance, Tax Haven has a significant effect on tax avoidance, and Thin Capitalization doesnt have significant effect on tax avoidance.